PERAN GURU PAI BP INTEGRATIF DALAM MEMBENTUK KARAKTER DAN KESADARAN BERAGAMA SISWA SEKOLAH DASAR - Dessy; Fadriati (LPPM Sekolah Tinggi Agama Islam Darul Falah, 2023)
This research discusses the role of Integrative PAI BP Teachers in Forming the Character and Religious Awareness of Elementary School Students. This research aims to determine the role of Islamic Education and Integrative Character teachers in shaping the character and religious awareness of elementary school students. The research method used in this research is descriptive qualitative research, namely using literature review (library research). In a library, data is obtained through examining related literature in the form of scientific journal articles, books, documents, as well as examining good works related to the discussion of this research.. The results of this research found that Islamic Religious Education (PAI) learning has an integrative approach in developing students' character. This approach includes aspects of morality, behavior, morals, character etiquette, character, character and psychological traits. Teachers, as the most determining element in the education system, have a big responsibility in developing students' religious awareness. External factors and internal factors influence the development of students' religious awareness, and both interact with each other. With good character education and positive influence from teachers, it is hoped that students will have a strong religious awareness and be able to apply religious values ​​in everyday life.